Ethics and chemistry: the role of learned societies, as exemplified by the German chemical societies. Issue 9 (20th October 2016) - Koch, Wolfram
Abstract : The times of the "ivory tower" are over; society expects that scientists accept their responsibility for the consequences of their research. In addition, due to numerous examples of significant misbehavior, scientists are increasingly judged by the general public whether they perform according to good scientific practice. Learned societies play an important role here, which, however, has changed since such societies were established more than 150 years ago. This article addresses these questions with a special focus on the situation in Germany.